Characterization and Antidiabetic Potential of Durian Leaf (Durio zibethinus Linn.) Ethyl Acetate Extract - Aruan, Dyna Grace Romatua; Barus, Tonel; Haro, Gindo; Simanjuntak, Partomuan (Chimica et Natura Acta, 2024)
Durian leaves (Duiro zibethinus Linn.) are one of the plants whose leaves are used as a fever reducer (antipyretic). The aim of this research is to isolate natural ingredients using natural ingredient extraction techniques by maceration and identify steroid compounds from durian leaves that have anti-diabetic potential. Isolation was carried out through several stages, namely maceration, fractionation, subfractionation using column chromatography, purification using preparative TLC, and testing the purity of the isolate using TLC and determining the melting point of the isolate. The antidiabetic potential of the isolation was carried out using the α-glucosidase enzyme inhibition method. The chemical structure of the isolate was characterized using IR and UV-Vis spectroscopy. Based on IR spectroscopy analysis, the isolation has C=C, OH, O-C functional groups, C-H aromatic functional groups. UV-Vis spectroscopy data shows that there are maximum peaks at 207 nm and 247 nm, meaning that the isolated steroid compound has unconjugated double bonds. Based on spectroscopic data and comparison with reference compounds, it could be identified that the isolate obtained was β-sitosterol.